A STUDY ON IMPLICATURE IN CONDOM COMMERCIALS USING RELEVANCE THEORY - PAMUNGKAS, JEFRI SATRIA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Condom Commercials, Relevance, Explicature, Higher-level Explicature, Implicature Condom commercials broadcasted in Indonesian television have uniqueness in delivering the messages. This phenomenon has encouraged the writer to analyze the implicature used in condom commercials. Pragmatic approach especially the theory of relevance is applied in this study. This study aims at analyzing the implicature used in condom commercials using relevance theory derived from explicature, higher level explicature, and implicature.The data source of this study was condom commercials broadcasted in Indonesian television. There were 13 data taken from 5 Sutra condom commercials, 7 Fiesta condom commercials, and 1 Durex condom commercial. The writer used qualitative approach with document analysis to analyze the relevance.This study revealed that in uncovering the implicature used in condom commercials, three stage processes were done. Explicature is used to give detailed explanation about the utterances uttered by the speakers helped by the context. In this study, the explicating process was derived via reference assignment and bridging. Deriving higher-level explicature is needed to find the propositional attitude toward the speakers’ utterances by analyzing non-linguistic aspects where in this study tone voice is used by the speakers. Deriving the implicature requires the viewers’ knowledge and the most suitable context which are represented in implicit premises that are constructed based on the context and implicated conclusion obtained by drawing conclusion from the whole process. It can be inferred that the implicit meaning coming from condom commercials are about introducing the products with their characteristics or specialties which differ from other competitors. The message about the importance of using condom before having sexual activities are also delivered by the advertisers. It is concluded that explicature, higher-level explicature, and implicature are interpreted by drawing inferences retrieved from the context, background knowledge, and assumptions.The next writers are recommended that they conduct similar studies aboutrelevance theory with different objects such as cigarette and birth pill controlcommercials broadcasted on television. The writer also suggests the televisionviewers understand deeply the message delivered in televsion commercials.